THE EPOCH OF DIGITAL: CHALLENGES TO THE CIVIL IDENTITY OF YOUTH - Коriakovtseva Olga; Bugachuk, Tatyana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article deals with the problem of the formation of civic identity in the epoch of digital. The authors emphasize the randomness of this process, defining it as an experiment, a “game” with social roles, statuses, and masks. The reasons for the similar nature of the identification of a person in modern society are revealed, which are associated with the erosion of virtuality and reality in the self-consciousness of young people.